Peran Konseling Pastoral dalam Menangani Mahasiswa yang Mengalami Toxic Masculinity di STT Ekumene Jakarta - Julianus Zai (LPPM - STT Kadesi Bogor, 2025)
This research aims to analyze the role of pastoral counseling in dealing with students who experience toxic masculinity at the Jakarta Ecumenical Theological College. Toxic masculinity is a patriarchal social construction that forms patterns of male behavior that emphasize violence, control and domination. This has a negative impact on students' mental health and interpersonal relationships. This research uses a qualitative method with a case study approach. Data collection was carried out through observation, interviews and documentation. Participants in this research were pastoral counselors, students, and related parties at the Jakarta Ecumenical Stt. The results of this research show that pastoral counseling has an important role in dealing with students who experience toxic masculinity. Pastoral counseling can help students understand the concept of healthy masculinity, develop self-awareness and learn to manage emotions and behavior constructively. In addition, pastoral counseling can also facilitate changes in student attitudes and behavior through a client-centered approach, emphasizing self-understanding, and building a safe and supportive therapeutic relationship.